Pengaruh Dimensi Kualitas Pelayanan terhadap Kepuasan Penumpang Kapal Laut pada Terminal Penumpang Gapura Surya Nusantara PT. Pelabuhan Indonesia (Persero) Regional 3 Tanjung Perak - Setiawan, Prisca Titan; Rumambi, Freddy Johanis (Neolectura, 2023)
This study was conducted to determine the effect of the dimensions of service quality provided by the Nusantara Pura Passenger Terminal belonging to PT Pelabuhan Indonesia (Persero) Regional 3 Tanjung Perak on passenger satisfaction and passenger confidence using passenger terminal services. Passenger satisfaction the dependent variables, and tangible, reliability, responsiveness, assurance, and empathy are independent variables. This research is a quantitative study whose analysis process uses Partial Least Square (PLS) with SmartPLS version 4.0 The population of this study is all ship passengers using the Passenger Terminal services in 2022. The number of samples who filled out questionnaires for observation were 100 peoples. respondents. The results showed that reliability, responsiveness and empathy had a positive and significant effect on passenger satisfaction in the Gapura Surya Nusantra Passenger Terminal of PT Pelabuhan Indonesia (Persero) Regional 3 Tanjung Perak.